Management of possible serious bacterial infections in young infants where referral is not possible in the context of existing health system structure in Mbeya, Tanzania: Experience and lessons from the end line assessment. - Esther Ngadaya; Alexander Manu; Mary Mmweteni; Dorica Burengelo; Doreen Philbert; Gibson Kagaruki; Kahabi Isangula; Mbazi Senkoro; Godfather Kimaro; Amos Kahwa; Fikiri Mazige; Felix Bundala; et al. (PLoS ONE)
Severe bacterial infections (SBIs) are a leading cause of neonatal deaths in low- and middle-income countries. World Health Organization's (WHO's) guideline for outpatient management of danger signs indicating possible serious bacterial infections (PSBI) when referral is not possible was adopted by three pilot district councils in Mbeya Region, in Tanzania (Busekelo, Kyela and Mbarali Districts) in 2018 (the PSBI project). This study documented changes in practice during the PSBI project, and lessons learned. A cross-sectional study was conducted using both qualitative and quantitative data collection methods between July 2021 and January 2022, post-implementation. The study participants comprised stakeholders, health workers, community health workers, and mothers/fathers/caregivers who had a young infant with PSBI. Study tools included record review, quantitative, in-depth, and key informant interviews. Quantitative data were analysed using STATA version 15 (STATACorp Inc., TX, USA), whereas qualitative data were analysed using a framework analysis approach. Our assessment showed that 2,228 young infants (0-59 days old) from the three districts were classified as having PSBI. The majority, 1,607 (72.1%) had fast breathing as the only danger sign, while 621 (27.9%) were classified as having severe illness. All 621 young infants with severe illness were counselled and offered referral to a higher-level health facility; however, only 174 of them (28%) accepted the referral. The remaining 447 severely ill infants, for whom referral was not possible, were treated at the primary health facilities with gentamicin injection and amoxicillin dispersible tablets (DT). When referral is not feasible, outpatient treatment for young infants with signs of PSBI is possible within existing health system in Tanzania, based on experience after this pilot project. However, successful scale-up of outpatient management for PSBI will require commitments from government and key stakeholders to strengthen healthcare systems.